Impurity profiling of amphetamine and methamphetamine using Gas Chromatography Mass Spectrometry (GCMS) harmonised methods - Wan Nur Syuhaila Mat Desa,; Dzulkiflee Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Impurity profiling of drug seizures is a scientific approach employed to understand drug trafficking networks thus has becoming increasingly important in criminal investigation. This paper presents the feasibility of using the Collaborative Harmonisation of Methods for the Profiling of AmphetamineType Stimulants (CHAMP) established by the European Commission authority for impurity profiling of amphetamine and methamphetamine samples. Both drugs were analysed using similar extraction procedure and analytical conditions. The impurities were extracted from an alkaline buffer solution (pH8.1) using toluene prior to gas chromatography-mass spectrometry (GC-MS) analyses. The results showed that the reproducibility of the method for detecting amphetamine and methamphetamine ranged between 7.4-8.9 and 6.2-8.4 %RSD, respectively. Identification of impurities was performed by referencing against the available MS databases as well as to previous reported impurity profiling studies. Phenyl-2-propanone (P2P), also known as benzyl-methyl-ketone (BMK), as well as other specific impurities such as 4-methyl-5-phenylpyrimidine, bis-(1-phynelisopropyl) amine, N-formylamphetamine and N,N-di (b-phenylisopropyl) amines were identified in the amphetamine samples, indicating Leuckart’s pathway as the route of synthesis. Because P2P was also detected in the methamphetamine samples, the possible route of synthesis of the methamphetamine samples being Leuckart’s, nitrostyrene synthesis or reductive amination could not be ruled out.